2021
DOI: 10.1038/s41385-020-0298-2
|View full text |Cite
|
Sign up to set email alerts
|

Group-2 innate lymphoid cell-dependent regulation of tissue neutrophil migration by alternatively activated macrophage-secreted Ear11

Abstract: Type-2 immunity is characterised by interleukin (IL)-4, IL-5 and IL-13, eosinophilia, mucus production, IgE, and alternatively activated macrophages (AAM). However, despite the lack of neutrophil chemoattractants such as CXCL1, neutrophils, a feature of type-1 immunity, are observed in type-2 responses. Consequently, alternative mechanisms must exist to ensure that neutrophils can contribute to type-2 immune reactions without escalation of deleterious inflammation. We now demonstrate that type-2 immuneassociat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 67 publications
(91 reference statements)
0
9
0
Order By: Relevance
“…As signature M2 macrophage genes, RELMα and Ym1/2 are reported to have equivalent expression patterns, but Ym1 can also promote RELMα expression ( 24 ). Ear11 is an eosinophil-associated ribonuclease that is secreted by M2 macrophages and promotes neutrophil chemotaxis ( 39 ). Consistent with IL-4 induced resident macrophage proliferation, genes associated with the cell cycle (Top2a, Cdc20, Kif20a, Ccnb2) were upregulated.…”
Section: Resultsmentioning
confidence: 99%
“…As signature M2 macrophage genes, RELMα and Ym1/2 are reported to have equivalent expression patterns, but Ym1 can also promote RELMα expression ( 24 ). Ear11 is an eosinophil-associated ribonuclease that is secreted by M2 macrophages and promotes neutrophil chemotaxis ( 39 ). Consistent with IL-4 induced resident macrophage proliferation, genes associated with the cell cycle (Top2a, Cdc20, Kif20a, Ccnb2) were upregulated.…”
Section: Resultsmentioning
confidence: 99%
“…Such modulation of neutrophils has likely emerged in evolution together with the emergence of type 2 immune responses and the IL‐4 and IL‐13 genes 32 . Notably, IL‐4–/IL‐13–mediated modulation of neutrophils is also shaped by the concomitant production of other factors in the tissue microenvironment, including other cytokines, chemokines, and anti‐microbial proteins, such as chitinase‐like proteins, eosinophil‐associated ribonucleases, and eosinophil‐associated cationic proteins 31,33 …”
Section: Discussionmentioning
confidence: 99%
“…Another study reported that type 2 immunoregulatory neutrophil infiltration is influenced by mouse eosinophil associated ribonuclease 11, and is secreted by M2 macrophages downstream of ILC2s that are stimulated by IL-25 (111). Furthermore, neutrophils can promote type 2 immune response without aggravating inflammation (111).…”
Section: Pulmonary Viral and Fungal Infectionsmentioning
confidence: 99%